Effects of adopting the Global Lung Function Initiative 2017 reference equations on the interpretation of carbon monoxide transfer factor. Issue 5 (28th May 2020) - Brazzale, Danny J.; Seccombe, Leigh M.; Welsh, Liam; Lanteri, Celia J.; Farah, Claude S.; Ruehland, Warren R.
The recently published Global Lung Function Initiative (GLI) carbon monoxide transfer factor ( T LCO ) reference equations provide an opportunity to adopt a current, all-age, widely applicable reference set. The aim of this study was to document the effect of changing to GLI from commonly utilised reference equations on the interpretation of T LCO results. 33 863 T LCO results (48% female, 88% Caucasian, n=930 aged <18 years) from clinical pulmonary function laboratories within three Australian teaching hospitals were analysed. The lower limit of normal (LLN) and proportion of patients with a T LCO below this value were calculated using GLI and other commonly used reference equations. The average T LCO LLN for GLI was similar or lower than the other equations, with the largest difference seen for Crapo equations (median: −1.25, IQR: −1.64, −0.86 mmol·min −1 ·kPa −1 ). These differences resulted in altered rates of reduced T LCO for GLI particularly for adults (+1.9% versus Miller to −27.6% versus Crapo ), more so than for children (−0.8% versus Kim to −14.2% versus Cotes ). For adults, the highest raw agreement for GLI was with Miller equations (94.7%), while for children it was with Kim equations (98.1%). Results were reclassified from abnormal to normal more frequently for younger adults, and for adult females, particularly when moving from Roca to GLI equations (30% of females versus 16% of males). The adoption of GLI T LCO reference equations in adults will result in altered interpretation depending on the equations previously used and to a greater extent in adult females. The effect on interpretation in children is less significant. Adoption of GLI T LCO reference equations in adults will result in altered interpretation depending on the equations previously used and to a greater extent in adult females. The effect on interpretation in children is less significant. http://bit.ly/3cmRzsY